EFEKTIFITAS PENGGUNAAN KERTAS LIPAT (ORIGAMI) DALAM MENINGKATKAN KREATIVITAS PADA ANAK - Kusumaningrum, Aprilia Dyah (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstrackÂ This research aims to know the effectiveness of the use of folding paper (origami) in enhancing creativity in children so that this research uses experimental methods with pretest-posttest control group design. A subject of study as much as 13 a student of class B RA Muslimat Grabag 2 Magelang having creativity with the category of low based on the pretest. A subject of study divided into two groups which is the experiment (n=7) and the control group (n=6). Instrument data used is the test creativity figural (TKF) and observation. Data gain score or difference between scores pretest posttest and obtained in research analyzed uses statistics nonparametrik with technique of statistical analysis using test mann-whitney u. This research result obtained standard significance of p = 0,03 (p < 0,05). This indicated that there are differences between groups gain score significant of his experiments with the control group. While the result of the test wilcoxon, in a group of experiments obtained p = 0,018 ( p < 0,05 ) and in the control group obtained p = 0,400 ( p > 0,05 ) that suggests that the group experiment obtained the result of a significant compared to the control group. From the results of the research it can be concluded that there is an influence of the use of folding paper (origami) which significantly to children´s creativity.Keyword : fold paper (origami), creativity, children